Influência do conteúdo orgânico na mobilidade de metais pesados em sedimentos do leito da rede de drenagem natural de microbacias urbanas no Cariri Cearense - Brito, Anielle dos Santos (2022)
The sediments of the beds of the watercourses keep in themselves the memory of the environment through which they pass, revealing the edaphic, geological and anthropic characteristics through the chemical elements impregnated in them. For this reason, studies of these sediments are useful in identifying, monitoring and controlling sources of pollution. Several biogeochemical reactions allow the fixation of pollutants in the sediment or mobilize them to the medium, depending on local conditions of pH, Eh and salinity. The present study aimed to investigate the intervening factors in the processes of mobilization/fixation of heavy metals in sediments from the natural drainage network of urban watersheds in Cariri, Ceará. For this, surface water and sediment samples were collected at six collection points distributed along the drainage system. Water collections were carried out at a distance of at least 0.50 m from the banks of streams and lakes to ensure that the samples were representative of the evaluated stretch. In the sediments, samples were collected 0.2 m from the surface and 0.30 m from the bed, taking care not to cause suspension. The surface water samples were characterized by the following parameters: chlorides, electrical conductivity, biochemical oxygen demand, chemical oxygen demand, dissolved oxygen, hydrogenion potential, redox potential, sedimentable solids, total suspended solids and temperature. In the sediment samples, the concentrations of water-soluble carbon, total and labile organic carbon, concentrations of metals (Cu, Cr, Fe, Mn, Ni, Pb and Zn), hydrogen and redox potentials and granulometric distribution were determined. From the results, the predominance of humin in the organic content was verified. Positive correlations were obtained between the total suspended solids of the water and the labile organic matter fractions of the sediment (SST/CL and SST/CSA) and between the redox potential (of the sediment) and the CL. Negative correlation was obtained between dissolved oxygen in water and CL. The PCA indicated a change in the organic content of water and bed sediments is associated with the different forms of use and occupation of the soil in the studied microbasins, mainly related to the suppression of riparian vegetation in areas surrounding the studied collection points and the precariousness of the sanitary sewage system in areas occupied by urban infrastructure. Points P2, P3, P4, P5 and P6 are located in areas of environmental interest, defined by the Urban Development Master Plan of the municipality of Juazeiro do Norte-CE as Special Zone 2 - ZE2 (P2, P4, P5 and P6) and Special Zone 3 - ZE3 (P3), which perform the important ecosystem function of ecological regulation, since they are related to the preservation and protection of water resources incident in this municipality.